Proceso de Atención de Enfermería en Paciente de 48 años de edad con: Cirrosis Hepática. - Conforme Bajaña, Diana Mercedes (2020)
The nursing care process constitutes the fundamental pillar to provide adequate care to patients suffering from various pathologies. Cirrhosis is characterized by the progressive destruction of the liver parenchyma and by alterations in the structure of the liver. Being a silent disease of slow process whose symptoms appear in advanced stages of the disease. The development of this clinical case was based on a 48-year-old patient with a medical diagnosis of liver cirrhosis, taking into consideration the needs according to Gordon's functional patterns, and Nanda, Noc and Nic taxonomic requirements, which allow adequate care that is beneficial for the patient through the application of Pae; The corresponding follow-up was carried out in which it consists of 6 days of evaluation and control from the application of the treatment to the patient, which shows the improvement until reaching the sixth day with a favorable evolution; what was evidenced in the hospital discharge process, put through the correct identification of the nursing care process, the patient can improve their quality of life.